2016
DOI: 10.5539/jas.v8n8p112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Striga hermonthica (Del.) Benth on Yield and Yield Components of Maize (Zea mays L.) Hybrids in Western Kenya

Abstract: Striga hermonthica (Striga) weed is widespread in Kenya, where it causes significant cereal crop losses, particularly when susceptible varieties are grown. The use of maize (Zea mays L.) genotypes that support reduced Striga hermonthica emergence can form an important basis for developing resistant cultivars. The objective of this study was to evaluate the response of diverse maize hybrids to Striga weed infestation and to identify high yielding and stable hybrids. Six experimental maize hybrids and three comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This shows that the low grain yields obtained in commercial susceptible varieties can be linked to effects of striga damages. Similarly, results showed that in areas where fewer striga shoots were attached to grain yield was high [27]. Low grain yield observed in Rangwe despite fewer striga shoots density was possibly linked to other factors such as low inherent soil fertility.…”
Section: Discussionmentioning
confidence: 67%
“…This shows that the low grain yields obtained in commercial susceptible varieties can be linked to effects of striga damages. Similarly, results showed that in areas where fewer striga shoots were attached to grain yield was high [27]. Low grain yield observed in Rangwe despite fewer striga shoots density was possibly linked to other factors such as low inherent soil fertility.…”
Section: Discussionmentioning
confidence: 67%
“…Nyahera lies at a longitude of 34°53.452′E, latitude of 0°35.977′N, and an altitude of 1490 m with an average annual rainfall of 1650 mm per annum. The soils are classified as ferralic with a pH of 5.9 (Mbogo et al, 2016). Kadel is found at a longitude of 34°24°E, latitude N-0°11'27" S, and an altitude of 1400 m above sea level with an average annual rainfall of 1200 mm (Ogenga et al, 2018).…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
“…Evaluation of genotypes at Nyahera site was carried out under natural Striga infestation in the short rains of September 2018 and both under Striga free and Striga infestation in the long rains of March 2019. Nyahera is a site that had been used for Striga research by various organizations such as Nairobi University and International Maize and Wheat Improvement Center (Mbogo et al, 2016), the site, therefore, had already established Striga plots and Striga free plots. At Kadel, successful evaluation of sorghum genotypes was carried out only in the long rains of March 2019 under natural Striga infestation, given that the whole site was Striga infested.…”
Section: Experimental Design and Field Layoutmentioning
confidence: 99%
“…Vatke, Striga hermonthica (Del.) Benth and Striga asiatica (L.) Kuntze is the most economically devastating weeds worldwide (Mbogo et al 2016). Striga weed causes global yield losses translating to more than 40 billion US$ (Jamil et al 2012), while in Sub-Saharan Africa, it results to yield losses of up to 100%, translating to approximately 7 billion US$ annually.…”
Section: Introductionmentioning
confidence: 99%
“…In Western Kenya, Striga is the greatest bothersome weed, it distresses cereal such as millet, maize, sugarcane, rice, and sorghum. It results to cereal yield loss of up to 81 percent in Western Kenya (Mbogo et al 2016). An assessment of 85 maize farms in Siaya County, shown that 73% of the field are infected by the weed, causing maize yield loss of 1.15 tons per hectare (MacOpiyo et al 2010).…”
Section: Introductionmentioning
confidence: 99%